Answer:
x = 3
y = 0
z = 8
Step-by-step explanation:
a) 3x + 3y - z = 1
b) z = 8
c) -x -3y + 2z = 13
a) 3x + 3y - 8 = 1 (substitution)
a) 3x + 3y = 9
c) - x - 3y + 2(8) = 13 (substitution)
c) -x - 3y + 16 = 13
c) -x - 3y = -3
(3x + 3y = 9) + (-x -3y = -3)
= 2x = 6
x = 3
a) 3(3) + 3y - 8 = 1
9 + 3y - 8 = 1
y = (1 -9 + 8)/3
y = 0
Step-by-step explanation:
5 x − 7 = 8 5x-7=8 5x−7=8. Add 7 to both sides. Simplify 8 + 7 8+7 8+7 to 1 5 15 15.
Answer:
V = 1046.9
Step-by-step explanation:
The equation for volume is (4/3)pi r^3
substitute 3.14 in for pi and 6.3 in for r so (4/3)*3.14*6.3^3
18 is an even number because if you divide 18 ÷ 2 = 9 it guves you an odd number
The answer for the completion exercise shown in the image attached above is:
1) Multilplication property of equality (If you multiply mEFG+mGDE=360° both sides of the equation by 1/2, you obtain 1/2(mEFG)+1/2(mGDE)=180°).
2) m∠D=1/2(mEFG)
3) m∠F=1/2(mGDE)
4) By the substitution property of equality (Because if you substitute m∠D=1/2(mEFG) and m∠F=1/2(mGDE) into 1/2(mEFG)+1/2(mGDE)=180°, you obtain: m∠D+m∠F=280°).